Analisis Dampak Perubahan Artefak Kebutuhan Berdasarkan Kedekatan Semantik Pada Pengembangan XP - Arrijal Nagara Yanottama; Siti Rochimah (Ikatan Ahli Informatika Indonesia (IAII), 2021)
The Extreme Programming (XP) development method is popular because of the flexibility of the development process, it can accommodate changes quickly. But this method has a weakness in terms of documentation. It is expected that the speed of discovering which parts of the source code need to be changed will be greatly improved by analyzing the impact of changes on the requirements document. In this study, a method of analyzing the impact of changes is proposed by tracing changes in the artifact of the need to find out the source code that occurs. Early language methods and semantic approaches are used. Based on the proximity of the semantics, it will be analyzed to find out the elements in the source code that use the Spearman Correlation Coefficient. The test dataset in this study consisted of the source code in the PHP programming language as well as the functional requirements of the software. Requirements change list is generated by analysis of the latest 2 (two) expert versions of the source code. The changing needs are described in a user story document. Based on the test results in this study, the average precision was 0.1725 and the average recall value was 0.6041.